Petrogenesis of diabase from accretionary prism in the southern Qiangtang terrane, central Tibet: Evidence from U-Pb geochronology, petrochemistry and Sr-Nd-Hf-O isotope characteristics - Li, J.; Qin, K.; Li, G.; Zhao, J.; Cao, Mingjian (Blackwell Publishing Asia, 2015)
© 2015 Wiley Publishing Asia Pty Ltd.The Bangong-Nujiang suture (BNS) between the Lhasa and Qiangtang terranes is an important boundary and its petrogenesis is controversial. Diabase from the accretionary prism in the southern Qiangtang terrane yields a zircon U-Pb age of 181.3±1.4Ma. All the diabases show tholeiitic basalt compositions, gentle enrichment patters of light rare earth elements (REE), variable enrichment in incompatible element concentrations (e.g. Th and Rb), and no anomaly in high field strength elements (e.g. Nb and Ta), similar to that of enriched mid-ocean ridge basalt (E-MORB). They have relatively homogeneous whole rock Nd (eNd(t)=7.3-9.1) and zircon Hf-O isotopic compositions (eHf(t)=14.8-16.1, and d18O=4.57-6.12‰), possibly indicating melting of the depleted mantle and no significant crustal contamination during the petrogenesis. The element variations suggest that the diabases were formed by plume-ridge interaction at a mid-ocean ridge within the Bangong-Nujiang ocean.